Born fi dead? Special collections and born digital heritage, Jamaica. (October 2015) - Smart, Cherry-Ann
Cultural heritage print items in special collections hold distinct positions in libraries. Yet their potential for pedagogy and learning may often be under-explored due to issues related to preservation management. These challenges underpin their exclusivity, a perception which may impact donor relations and unconsciously impede research access. Conversely, electronic publishing has enhanced access to born digital cultural heritage products of scholars and creative expressionists. Without the hassle of intermediaries, these born digital producers represent a "new world order" for libraries charged with dual responsibility for access and posterity. Some challenges are infrastructural, such as Internet penetration, others are human related arising from the need for capacity building in areas such as publishing and effective preservation strategies. These skills are essential to fully conceptualize potential for loss of cultural heritage products and the need for viable mechanisms to manage content; anything less would suggest cultural heritage products are literally "born fi dead".